Efficacy of Seed Treatment with the Mixture of Acetamiprid + Fipronil for Controlling Aphis gossypii Glover (Hemiptera: Aphididae) - Pereira, Marcelo Francisco Arantes; Borges, Rodrigo dos S.; Justo, Célio Luiz; Paschoal, Danila de Cássia (BioAssay, 2011)
The cotton aphid, Aphis gossypii Glover (Hemiptera; Aphididae), is one of the main cotton crop pests and the use of insecticides is important in its control. The objective of this study was to evaluate of the efficiency of mixture of acetamiprid and fipronil insecticides, in dry cotton seed coating, in controlling A. gossypii aphids. The experimental design was of randomized plots with seven treatments and four replications. Cotton seeds, from cv. Delta Opal, were submitted to the following treatments – at g of active ingredient (AI).100kg-1 of seeds: acetamiprid+fipronil - 200+50, 240+60 e 280+70, acetamiprid – 210, fipronil - 70, tiametoxam - 210 and control (without insecticide). After plants emergency, aphids on leafs of ten plants per plot were evaluated. The pest population was least on cotton crop under seed treatment with acetamiprid+fipronil, acetamiprid and tiametoxam. The mixture of acetamiprid and fipronil was effective in controlling A. gossypii in cotton crop, even at 200+50 g AI.100kg-1 of seeds, by causing 93, 82 and 93% of mortality, at 11th, 15 th and 21th days after seedling emergence, respectively.